Performa Ayam Kampung Pada Pemeliharaan Intensif Di Kecamatan Salahutu - Tutubun, Gloria A.; Papilaya, Bercomien J.; Rajab, Rajab (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to determine the performance of native chickens cultivated by breeders in an intensive rearing system in Salahutu District, Central Maluku Regency. The research method is survey and observation through direct observation and measurement of data related to native chicken performance. The materials used as samples in this study were 71 native chickens aged 6-7 months. The observed variable was the performance of native chickens in intensive rearing. The results showed that the average male body weight was 2059.667 grams and 1163.88 grams for females; the average wing length of males is 16.46 cm and females is 15.45 cm; the average male chest circumference is 30.81 cm and 27.72 cm for females; the average femur length of males is 12.39 cm and females are 6.98 cm; the average tibia length is 14.95 cm for males and 13.07 cm for females; and the average metatarsus length of males is 10.09 cm and females is 8.07 cm. While the average distance between the pubic bones of hens is 3.56 cm with egg production reaching 22.1 eggs/30 days of production. The performance of free-range chickens is still diverse but better than traditional and semi-intensive farming systems.